TANDA BAHAYA SERTA PENATALAKSANAAN PERDARAHAN POST-PARTUM - Windu Sanjaya (Intisari Sains Medis, 2015)
Post-partum hemorrhage defined by WHO by condition loss of blood >500 ml of 24 hours after labor. Based on research in 2008, said every women that died in minute on labor, that 24% caused by massive hemorrhage. Diagnosis of post-partum hemorrhage acquired by seeking the cause of hemorrhage, calculate the blood loss and patient clinical condition. Treatment of post partum hemorrhage started by giving uterotonic, uterine massage, bimanual compression, blood transfusion/ crystalloid fluid, giving blood coagulation factor, and/or retain rest placenta manually and trauma management. Invasive treatment such are balloon tamponade, uterine compressed hecting, angiographic arterial embolization, arterial ligation, and hysterectomy. Some modified technic also very suggested to be able to performed in area with limited facilities. Prevention of post-partum hemorrhage are by perform management active phase III, knowing the risk factor and always do consultation with competent medical staff.